Long-Term Effects of Balance Training on Habitual Physical Activity in Older Adults with Parkinson’s Disease - Håkan Nero; Erika Franzén; Agneta Ståhle; Martin Benka Wallén; Maria Hagströmer (Parkinson's Disease)
The HiBalance program is a progressive and highly challenging balance training intervention incorporating Parkinson’s disease (PD) specific balance components. The program improves balance and gait and increases the amount of ambulation in short-term, in older adults with PD. Yet, potential short- and long-term effects on habitual physical activity and sedentary behavior are currently unidentified. The aim of this study was to conduct preplanned secondary analyses of short- and long-term effects of the HiBalance program on objectively measured amount and bouts of brisk walking, sedentary behavior, and total physical activity in older adults with PD. Further, our aim was to investigate demographic, intervention-related, disease-related, and function-related factors potentially related to a difference in activity after intervention. A total of 100 older adults with mild-moderate PD were recruited. The intervention group participated in the HiBalance program, and the control received care as usual and was offered the HiBalance program after study termination. Physical activity data were collected using accelerometers at baseline, after intervention and after 6 and 12 months. A multilevel model was utilized to investigate the postintervention and long-term (6 and 12 months) effects on total physical activity, amount and bouts of brisk walking (i.e., moderate intensity physical activity), and sedentary behavior. Between-group difference for the main outcome brisk walking was at postintervention: Δ −10, CI −23.78 to 3.69 min/day (p<0.05); 6 months: Δ −10, CI −23.89 to 3.89 min/day (p<0.05); and 12 months: Δ −4, CI −16.81 to 8.81 min/day (p=0.43). Being part of the intervention group as well as finishing training during spring/summer showed an independent association to increased brisk walking after the intervention period. In conclusion, the HiBalance program increases the physical activity on moderate intensity after intervention and at 6 months but not at 12 months, independently of improved balance. Season seems to influence the effect on the physical activity.